معوقات البحث العلمي لدى طلبة معهد علوم وتقنيات النشاطات البدنية و الرياضية المسيلة - طيار, اسامة (My University, 2020)
ملخص: موضوع بحثنا أساسه التعرف على معوقات البحث العلمي لطلبة السنة الثانية ماستر النشاط البدني الرياضي التربوي، والكشف عن المعوقات التي تعترض الطلبة؛ كما حاولت الد ا رسة الحالية الإجابة عن التساؤلات المتعلقة بمختلف معوقات البحث العلمي الطلبة النشاط البدني الرياضي التربوي ، والمعوقات الأكثر أهمية وتأثير لديهم. وبعد تحليل وإثراء متغيرات الدراسة نظريا، واستخدام أداة لقياس معوقات البحث العلمي لطلبة النشاط البدني الرياضي التربوي ، والتأكد من تمتع أداة القياس التي استخدمت في البحث الحالي بالخصائص السيكوميترية اللازمة، طبقت على عينة الدارسة المكونة من 60 طالب ، وزع عليهم استبيان معوقات البحث العلمي لطلبة النشاط البدني الرياضي التربوي حيث تم اعتماد المنهج الوصفي التحليلي. وبعد جمع البيانات ومعالجتها إحصائيا وعرضها ومناقشتها توصلت نتائج البحث الحالي أن طلبة النشاط البدني الرياضي التربوي لديهم العديد من معوقات البحث العلمي بين درجة كبيرة ودرجة كبيرة جدا وذلك وفقا لمجالات درجة معوقات البحث العلمي لدى الطلبة المقترح، وذلك على كل محاور الاستبيان الثلاثة. بالإنجليزية : Abstract: The topic of our research is based on identifying obstacles to scientific research for second-year students of the Master of Physical, Sports and Educational Activity, and revealing the obstacles encountered by students. The current study also attempted to answer questions related to the various obstacles to scientific research for students, physical, sports, and educational activities, and the most important and influential obstacles to them. After analyzing and enriching the study variables theoretically, and using a tool to measure the obstacles to scientific research for students of educational physical and sports activity, and to make sure that the measurement tool used in the current research has the necessary psychometric properties, it was applied to the study sample consisting of 60 students, and a questionnaire for scientific research obstacles was distributed to them for the students of the Physical, Sports and Educational Activity, where the descriptive analytical approach was adopted. After collecting data, treating them statistically, presenting them and discussing them, the results of the current research concluded that students of educational sports physical activity have many obstacles to scientific research, between a large degree and a very large degree, according to the areas of the degree of obstacles to scientific research among the proposed students, on all three axes of the questionnaire.
Keywords: معوقات البحث العلمي; البحث العلمي; طلبة معهد علوم وتقنيات النشاطات البدنية